The role of the transition to the Latin alphabet in Kazakhstan in the modernization of the state language - Mukhataeva К.; Maikotova Ғ.; Mergenbayeva Қ. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Since the beginning of independence, many proposals have been made and discussed in our country regarding the transition to the Latin alphabet. After the adoption of the Law on the transition to the Latin alphabet, the views and analysis of ordinary citizens and representatives of the intelligentsia of our republic were made public. If one to look at the historical precedents, it becomes clear that it is not easy to change the alphabet of any country. But although this is beneficial to the colonial countries, it leads to a slowdown in the development of political, economic, historical, cultural and national values of local peoples. Therefore, by decision of the Soviet government in 1929-1940, the first Decree was adopted in the Kazakh SSR on the introduction of a new alphabet based on the Latin alphabet. As for the Alash intelligentsia, they perfectly understood the negative consequences of such a mission and wanted the Kazakh people to have their own alphabet. The project of the national leader Ahmet Baitursynuly “Cursive writing” also did not last long. Those who opposed the Latin alphabet were accused and persecuted. The purpose of the article is to highlight a number of problems occurring in our society in connection with the romanization of the Kazakh alphabet. During the study of the topic of the article, along with empirical methods, such as description, observation and comparison, theoretical methods were used based on the opinions of prominent figures of the country and research and conclusions in the works of foreign scientists. The proposed scientific article is intended for domestic and foreign undergraduates and doctoral students, as well as linguists and researchers who study in detail the process of the transition of Kazakh graphics to the Latin alphabet.